2020
DOI: 10.1093/femsre/fuaa009
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Bacterial DNA Double-Strand Break Repair Proteins in Chromosomal DNA Replication

Abstract: It is well established that DNA double-strand break (DSB) repair is required to underpin chromosomal DNA replication. Because DNA replication forks are prone to breakage, faithful DSB repair and correct replication fork restart are critically important. Cells, where the proteins required for DSB repair are absent or altered, display characteristic disturbances to genome replication. In this review, we analyze how bacterial DNA replication is perturbed in DSB repair mutant strains and explore the consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 142 publications
5
39
0
Order By: Relevance
“…Since the discovery of the RecD role in cold-adaptation, a quest to understand DNA-repair processes at low temperature has revealed the importance of DNA-repair genes such as recC, recB, recF, recO, recR, recJ, and ruvAB in cold adaptation of P. syringae (Pavankumar et al, 2010;Sinha et al, 2013;Sinha et al, 2020). As described in this section, the RecBCD-and…”
Section: Role Of the Recfor Pathway In Dna Repairmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the discovery of the RecD role in cold-adaptation, a quest to understand DNA-repair processes at low temperature has revealed the importance of DNA-repair genes such as recC, recB, recF, recO, recR, recJ, and ruvAB in cold adaptation of P. syringae (Pavankumar et al, 2010;Sinha et al, 2013;Sinha et al, 2020). As described in this section, the RecBCD-and…”
Section: Role Of the Recfor Pathway In Dna Repairmentioning
confidence: 96%
“…In E. coli, RecBCD and RecFOR pathways are the two major DNA repair-pathways that repair DSBs and single-strand DNA gaps via homologous recombination (Spies and Kowalczykowski, 2005;Sinha et al, 2020). (Ivancic-Bace et al, 2005;Sinha et al, 2020).…”
Section: Role Of the Recfor Pathway In Dna Repairmentioning
confidence: 99%
“…Faithful damage repair orchestrated by DNA repair proteins is essential to maintain genomic integrity, chromosomal replication and cell viability. Accordingly, mutants lacking repair proteins are sensitive to DNA damaging agents and are less viable ( Van Houten, 1990 ; Kuzminov, 1999 ; Sinha et al, 2020 ). Since (p)ppGpp binding to RNAP in E. coli destabilizes the open promoter complexes, it is expected to modulate replication-transcription collision and to play a role in maintaining genomic integrity.…”
Section: Role Of the Stringent Response In Dna Damage And Repairmentioning
confidence: 99%
“…The observation that loss of both RelA and SpoT (ppGpp 0 strain), i.e., inability to synthesize (p)ppGpp, enhanced UV sensitivity of an E. coli ruvAB mutant, suggested a possible role of (p)ppGpp in facilitating DNA repair ( McGlynn and Lloyd, 2000 ). RuvAB along with RuvC play a role in branch migration and resolution of Holliday junctions, formed during RecBCD-RecA-mediated DNA double-strand break (DSB) repair and RecFOR-RecA-mediated gap repair ( Kuzminov, 1999 ; Sinha et al, 2020 ). Interestingly, a slight increase in the basal level of (p)ppGpp by using the spoT1 allele, having reduced (p)ppGpp hydrolytic activity, improved UV survival of the ruvAB mutant ( McGlynn and Lloyd, 2000 ).…”
Section: Role Of the Stringent Response In Dna Damage And Repairmentioning
confidence: 99%
“…It has also been suggested that extended RNAP backtracking could be associated with R-loop formation from the 3'-end of the nascent RNA (40,46). R-loops are physiological initiators of ColE1 plasmid replication (47), but in addition their excessive occurrence (as in rnhA mutants) can lead to pathological initiation of chromosomal DNA replication in both bacteria (reviewed in [48][49][50] and eukaryotes (51). Such aberrant replication in bacteria is referred to as constitutive stable DNA replication (cSDR) since, unlike ordinary chromosomal replication which is initiated at oriC with the aid of the unstable protein DnaA, it continues long after inhibition of protein synthesis in the cells.…”
Section: Introductionmentioning
confidence: 99%